Erratum: Shoulder kinetics and ultrasonography changes after performing a high-intensity task in spinal cord injury subjects and healthy controls - Gil-Agudo, A; Mozos, M S; Crespo-Ruiz, B; del-Ama, A J; Pérez-Rizo, E; Segura-Fragoso, A; Jiménez-Díaz, F (Spinal cord, 2017)
Correction to: Spinal Cord (2016) 54, 277–282; doi:10.1038/sc.2015.140; published online 18 August 2015 Since the publication of this article, the authors have noticed that the author name ‘B Crespo-Ruiz’ was displayed incorrectly. The authors apologise for any inconvenience caused.